Pulai (Alstonia scholaris) was classification as IV-V for strenght class and V for durability class. This means that pulai has a low quality. One effort to improved the quality of pulai wood was densification process. This research aimed to evaluation the physical, mechanical and durability of pulai wood before and after densification process and to evaluated the temperature and pressing time on resulted the best quality of pulai wood. Densification was conducted on 160 °C and 180 °C with thre - ARINANA .; Farah DIBA (Departemen Hasil Hutan, IPB, 2009)
Pulai (Alstonia scholaris) was classification as IV-V for strenght class and V for durability class. This means that pulai has a low quality. One effort to improved the quality of pulai wood was densification process. This research aimed to evaluation the physical, mechanical and durability of pulai wood before and after densification process and to evaluated the temperature and pressing time on resulted the best quality of pulai wood. Densification was conducted on 160 °C and 180 °C with three pressing time 40 minute, 50 minute and 60 minute respectively. Densification targetted was 30%. Physical and mechanical process was conducted based on British Standard Methods No. 373 (1957), meanwhile durability test against subterranean termites was conducted with modified wood block test methods. Result of the research showed that densified pulai wood has the highest quality on physical, mechanical and durability properties than pulai wood control. The best densified treatment was on 180 °C with pressing time 60 minute. Densification process has improve the quality of pulai wood on one level class. Keywords : Alstonia sp, densification process, Coptotermes curvignathus